Growing the Entrepreneurial Spirit of Santri through the Independent Santri Program at Dayah Mahyal Ulum Al-Aziziyah - Mahlel Mansur (Wasatha: Jurnal Studi Islam dan Humaniora, 2023)
Indonesia's problem today is economic growth that is not accompanied by job opportunities. In addition, there are many opportunities and investment opportunities that are not supported by qualified human resource capabilities. As a result, a gap arises between the need for employment and the opportunities provided by business actors to the labor force, which in turn causes a large number of unemployed. This type of qualitative research is used with a descriptive approach. Sources of data are classified into primary data and secondary data. Data collection methods are interviews and documentation according to the required data. Data analysis techniques are descriptive techniques by making systematic and actual descriptions. The results of the research in cultivating the entrepreneurial spirit of Santri are providing entrepreneurship training with several models of entrepreneurship training systems. Entrepreneurship training activities at Dayah Mahyal Ulum Al-Aziziyah Aceh Besar, get positive implications from the students who take part in the training activities, so that the goals and desires of Dayah Mahyal Ulum Al-Aziziyah Aceh Besar are to foster the entrepreneurial spirit of the students and the attitude of independence of the students is achieved, although it still looks many deficiencies that must be corrected.